ANALISIS KESTABILAN LUBANG BUKAAN DENGAN METODE RMR-SYSTEM PADA LUBANG PENDIDIKAN JALUR J.3F – J.37 UNDERGROUND MINE PT. BUKIT ASAM OMBILIN SAWAHLUNTO - Wahyudi Saputra; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
The strength and shape of rock masses can be affected by tunnel excavation, so rocks will seek a new equilibrium as a result of such treatment. The displacement of tunnel walls and roofs, the occurrence of collapses in tunnels are signs of the rock's tendency to seek a free field where it can deform and allow a new equilibrium to be established.Using a method based on Bieniawski 1989, the RMR-System was used to weight the different rock mass classes. In this analysis, rock grades are weighted based on the compressive strength characteristics of the rock, Rock Quality Designation, discontinuity distance, groundwater conditions, and orientation of the bristles towards the tunnel. Rock mass class values, rock strength, collapse potential, holding time values, and buffer recommendations based on rock mass class values are the outputs of this analysis.Based on the measurements made for various parameters of the RMR method, the claystone at the J.3F - J.37 opening is in class III (fair rock) with an RMR value of 59, and the coal is in class III (fair rock) with an RMR value of 53. The stress values received at the cap and side post are 604.01 kg/cm2 and 150.67 kg/cm2, respectively, with a wood bending strength value of 800 kg/cm2 and a wood compressive strength of 470 kg/cm2.The recommended design of the three piece set wooden support is the length of the cap of 2.9 m, the bottom width of 3.4 m, the height of 2.4 m, the distance between the supports of 0.7 m, the diameter of the support of 18 cm with the FK value on the cap of 1.51. Meanwhile, the distance between supports of 1.2 m uses wood with a diameter of 22 cm with an FK value on the stamp of 1.61.